Principal instructional leadership as a driver for improving learning quality and outcomes - Muhammad Suryadi Syarif; Sri Nevi Gantini; Gilang Kumari Putra; Chukwuka Judith Nkolika (HAMKA INSIGHT, 2026)
Purpose: This study investigates the influence of principals' instructional leadership on student learning outcomes, specifically addressing suboptimal academic performance by examining the mediating role of learning quality in secondary education. Method A quantitative survey research design was conducted among secondary school teachers. Data were collected using validated, highly reliable questionnaires and analyzed via Structural Equation Modeling (SEM) to evaluate structural direct and indirect effects. Findings Results demonstrate that principals' instructional leadership exerts a statistically significant positive effect on learning quality, which directly enhances student outcomes. Moreover, empirical evidence confirms that learning quality serves as an effective mediating variable between instructional leadership and academic achievement. Practical implications This research provides actionable insights for educational practitioners and policymakers to design targeted leadership development programs, strengthen academic supervision, and cultivate teacher professional development to systematically improve student outcomes. Originality/value: This paper offers novel empirical validation elucidating the critical mediating pathway of learning quality, enriching the educational management literature by explaining precisely how principal leadership translates into improved student success